Innovating Indonesian Islamic Elementary English Education through A 5c Skills-Oriented Digital Game Application - Kholis, Adhan; Abadi, Anis Susila; Meilani, Rini Intansari; Sholihah , Akhris Fuadatis; Al Amri , Afan Welman (UIN Salatiga, 2025)
Today's education aims to equip students with the 21st-century skills necessary for success in a world shaped by globalization and technological advancement. These skills include creativity, collaboration, critical thinking, communication, and complex problem-solving. In the context of teaching English to young learners, particularly in Islamic elementary schools, integrating a game-based approach into the classroom proves to be an effective strategy. This approach fosters an engaging and dynamic learning environment that can incorporate all the necessary skills within the language learning process. However, traditional game-based methods often rely on physical or paper-based games that lack interactivity, scalability, and integration with digital literacy, which is a key aspect of 21st-century learning. These methods also tend to be teacher-centered, limited in content variety, and less motivating for digital-native students. This study aims to develop a 5C skills-based English learning game application using the Research and Development (R&D) method. To achieve this, the study employed the ADDIE model, including needs assessment, to analyze elementary school students' needs, wants, and challenges in learning English. This analysis forms the basis for developing the application, as well as its design, development, implementation, and evaluation. Data were collected through interviews and questionnaires. The results of thematic and descriptive statistical analyses revealed the importance of digital game media in actively engaging students and motivating them in their learning. The experiment demonstrated a significant difference in outcomes between students taught through traditional methods and those using digital games. This study suggests the necessity of incorporating digital games in English language learning as a valuable tool that every teacher should consider.